Fenómeno de Koebner The Koebner phenomenon - R E Achenbach (Asociación Argentina de Dermatología, 2011)
Descrito en 1871 por Heinrich Koebner, su fenómeno es uno de los más conocidos en la Dermatología. Koebner lo describe en un paciente con psoriasis que sufrió escoriaciones múltiples y una mordedura de caballo. Su figura fue una de las más destacadas en la Dermatología del siglo 19. Se revisa la lista de entidades con fenómeno Koebner y sus variantes, los tipos de injurias y su patogenia. First described in 1871, the Koebner phenomenon is one of the most well-known entities in dermatology. Heinrich Koebner is credited with the first adequate description of this peculiar disposition of psoriatic skin. He was one of the outstanding dermatologists of the 19th Century and reported the formation of psoriasiform lesions in uninvolved skin after excoriations and horse bites. Types of Koebner response, a list of injuries capable to produce it and a review of the pathogenesis are reviewed.